Evaluation of Nonviral piggyBac and lentiviral Vector in Functions of CD19chimeric Antigen Receptor T Cells and Their Antitumor Activity for CD19+ Tumor Cells - Lin, Zhicai; Liu, Xiangzhen; Liu, Tao; Gao, Haixia; Wang, Sitong; Zhu, Xingli; Rong, Lijie; Cheng, Jingbo; Cai, Zhigang; Xu, Fu; Tan, Xue; Lv, Linjie; et al. (Frontiers in Immunology, 2022)
Nonviral transposon piggyBac (PB) and lentiviral (LV) vectors have been used to deliver chimeric antigen receptor (CAR) to T cells. To understand the differences in the effects of PB and LV on CAR T-cell functions, a CAR targeting CD19 was cloned into PB and LV vectors, and the resulting pbCAR and lvCAR were delivered to T cells to generate CD19pbCAR and CD19lvCAR T cells. Both CD19CAR T-cell types were strongly cytotoxic and secreted high IFN-γ levels when incubated with Raji cells. TNF-α increased in CD19pbCAR T cells, whereas IL-10 increased in CD19lvCAR T cells. CD19pbCAR and CD19lvCAR T cells showed similar strong anti-tumor activity in Raji cell-induced mouse models, slightly reducing mouse weight while enhancing mouse survival. High, but not low or moderate, concentrations of CD19pbCAR T cells significantly inhibited Raji cell-induced tumor growth in vivo. These CD19pbCAR T cells were distributed mostly in mesenteric lymph nodes, bone marrow of the femur, spleen, kidneys, and lungs, specifically accumulating at CD19-rich sites and CD19-positive tumors, with CAR copy number being increased on day 7. These results indicate that pbCAR has its specific activities and functions in pbCAR T cells, making it a valuable tool for CAR T-cell immunotherapy.